Learning through monitoring, evaluation and adaptations of the 'Outcome Harvesting' tool - Blundo Canto, Genowefa M.; Läderach, Peter R.D.; Waldock, JaneLee; Camacho, Kemly (EDP Sciences, 2017)
This paper analyses a monitoring, evaluation and learning (MEL) system developed within an agricultural research for development institution. The system applies aspects of the Outcome Harvesting tool and focuses on learning for adaptation and improvement of innovation processes. Developmental evaluation principles are applied to discuss its application. The MEL system provides insight into the processes and interactions with next users that generate outcomes. MEL systems that use customized Outcome Harvesting aspects appear promising for adaptive management and to improve how research interacts with next users to achieve developmental outcomes.